Understanding the second wave of epidemics using the susceptible-infectious-recovered model - Butta, Raman; Butta, Shristi; Gupta, Manoj Kumar (International Journal of Research in Medical Sciences, 2021)
The world is currently reeling under the COVID-19 pandemic and secondary waves of the same are occurring in different countries. In the current paper, the authors try to explain the exact mathematical concept of a second wave based on their analysis of the popular SIR (susceptible-infectious-recovered) model in epidemiology. Effort is made to graphically and mathematically illustrate the natural infection curve, the necessity of austerity measures, the effects of such measures on the infection curve and the possible reasons for a second wave. The risk of quick mutation and need for effective vaccination is also discussed. It is believed that this analysis will be of immense help to scientists, doctors and policy-makers to devise proper strategies to urgently control the current COVID-19 pandemic, especially in countries where virus variants and secondary waves are occurring.